International Year of Planet Earth 7. Oceans: Submarine Landslides and Consequent Tsunamis in Canada - Mosher, David (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2009)
SUMMARY Canada has the longest coastline and largest continental margin of any nation in the World. As a result, it is more likely than other nations to experience marine geohazards such as submarine landslides and consequent tsunamis. Coastal landslides represent a specific threat because of their possible proximity to societal infrastructure and high tsunami potential; they occur without warning and with little time lag between failure and tsunami impact. Continental margin landslides are common in the geologic record but rare on human timescales. Some ancient submarine landslides are massive but more recent events indicate that even relatively small slides on continental margins can generate devastating tsunamis. Tsunami impact can occur hundreds of km away from the source event, and with less than 2 hours warning. Identification of high-potential submarine landslide regions, combined with an understanding of landslide and tsunami processes and sophisticated tsunami propagation models, are required to identify areas at high risk of impact.